Knowledge, attitude, and practice towards diabetes mellitus among Chiro town population, Eastern Ethiopia - Wondimagegn Wolde; Abel Desalegn Demeke; Daniel Atle; Dechasa Girma; Samuel Hailu (BMC Public Health)
Abstract Background Diabetes mellitus is a metabolic disorder with multiple etiological factors characterized by chronic hyperglycemia and disturbance of carbohydrate metabolism. It can play a vital role in the cause of morbidity and mortality through continued clinical consequences and mortality. Therefore, good knowledge of diabetes mellitus prevention and management is necessary for promoting care and enhancing good therapeutic outcomes. Objective To assess the knowledge, attitude, practice among the general population regarding diabetes mellitus in Chiro town, Eastern Ethiopia, from August 01 to October 30, 2023. Methods A cross-sectional study was conducted on 764 subjects. A pre-tested structured questionnaire was used to collect the socio-demographic information of the study participants. Data was entered into the Statistical Package for Social Science, checked for completeness and analyzed. The characteristics of the study population were summarized using descriptive statistics, frequency and percentage. Result The study revealed that 98% of respondents had heard of diabetes, with 80% identifying it as a condition of high blood sugar and 25% recognizing inadequate insulin action as a characteristic. Additionally, 65.57% demonstrated good knowledge of diabetes, 60% had a positive attitude towards diabetes management, and 35.4% reported good practices. Despite these insights, misconceptions persisted, such as 25% believing diabetes is caused by a curse. Regular exercise and non-smoking were common positive practices, but only 10.4% regularly checked their blood sugar levels. Conclusion and recommendation This study highlights high diabetes awareness (98%) but incomplete understanding. Mixed perceptions about diabetes management and significant gaps in prevention practices emphasize the need for targeted educational programs. These programs should focus on improving understanding of diabetes treatability, promoting regular monitoring, and encouraging healthier lifestyle choices. Enhanced awareness of comprehensive diabetes care, including proper medication use and physical activity, is essential for better prevention and management.